2022
DOI: 10.1038/s41598-021-04013-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation of fruit and ecophysiological traits among maqui (Aristotelia chilensis [Molina] Stuntz) provenances established in a common garden

Abstract: The domestication of forest species has traditionally relied on productivity issues. However, today there are concerns about the potential responses of natural populations and new cultivars to extreme climatic conditions derived from climate change and how to incorporate this knowledge into the domestication programs. Aristotelia chilensis (Molina) Stuntz (‘Maqui’) is a widely distributed native species in Chile. Its berry is considered a “super fruit” with an increasing interest in the food industry. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Therefore, we can suggest that SA could improve fruit growth and yield, decreasing oxidative stress and ABA levels in A. chilensis plants subjected to water deficit. It is important to highlight that we found higher fruit quality and yield parameters (by about 15%) compared to A. chilensis plants irrigated at 100% of evapotranspiration, as reported in Yañez et al [ 31 ] and González et al [ 47 ]. The authors analyzed fruits of plants from different geographical provenances but established in the same experimental garden (Maule Region, Chile), which showed the high genetic diversity in A. chilensis .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Therefore, we can suggest that SA could improve fruit growth and yield, decreasing oxidative stress and ABA levels in A. chilensis plants subjected to water deficit. It is important to highlight that we found higher fruit quality and yield parameters (by about 15%) compared to A. chilensis plants irrigated at 100% of evapotranspiration, as reported in Yañez et al [ 31 ] and González et al [ 47 ]. The authors analyzed fruits of plants from different geographical provenances but established in the same experimental garden (Maule Region, Chile), which showed the high genetic diversity in A. chilensis .…”
Section: Discussionsupporting
confidence: 85%
“…crop management, morphological and physiological characterization to improve its domestication and agronomic practices [31,37,38]. In a previous study, we [39] reported that foliar 0.5 mM SA application improved plant water status, photosynthesis, and plant growth in A. chilensis plants subjected to 40% of deficit irrigation compared to non-SA-treated plants under greenhouse conditions.…”
Section: Environmental Conditions Applied Water and Plant Water Statusmentioning
confidence: 93%
See 2 more Smart Citations
“…Variability in germination among populations was reported in other forest species and shrubs [ 58 , 59 , 60 , 61 ] and is attributed to genetic differences and climatic and geographic effects [ 62 ]. The Mediterranean-type climate area of central Chile has a diversity of climatic conditions due to its geography and latitudinal variation in germination capacity and early performance was observed in species of the Nothofagus genus [ 61 , 63 , 64 ] and sclerophyllous species including C. alba [ 37 , 65 , 66 ]. In our study, the success of seed germination and survival of C. alba was significantly determined by the seed source, where only the local seed source CA showed some survival at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%